Pengaruh karakteristik ibu terhadap munculnya pekerja anak di Indonesia tahun 2018 - Gratiana Imelda Nahak; Hardius Usman (Jurnal Kependudukan Indonesia, 2022)
The issue of child labor remains unresolved in Indonesia, hindering the achievement of one of the United Nations' Sustainable Development Goals (SDGs), which is to end child labor in all forms by 2025. This study aimed to examine the characteristics of child laborers aged 10-17 years old and the impact of maternal characteristics on child labor in Indonesia in 2018. The study analyzed data from the 2018 Indonesian Central Bureau of Statistics (Susenas KOR) survey using binary logistic regression. The results showed that most child laborers had mothers who were heads of households, had low levels of education, were disabled, had severe illnesses, were of productive age, had previously been married, and were recent migrants. It was concluded that maternal position in the household, maternal education level, maternal health status for severe illnesses, maternal age, and migration status significantly affected the prevalence of child labor in Indonesia in 2018. On the other hand, maternal physical condition, health status for mild illnesses, and marital status did not have an impact on child labor in Indonesia in 2018.